Production and Immobilization of Halophilic Invertase Produced from Honey Isolate Aspergillus niger EM77 (KF774181) - Esawy, Mona Abdeltawab; Kansoh, Amany Lotfy; Kheiralla, Zeinab Hassan; Ahmed, Hala Elmonem; Kahil, Tarek Aly-Kamal; El-Hameed, Eman Karam (International Journal of Biotechnology for Wellness Industries, 2014)
Honey isolate Aspergillus niger EM77 was a good halophilic invertase producer in the presence of wheat bran as a complete medium (114.55 U/g), using solid state fermentation technique. Different parameters influence the enzyme productivity such as different pH values, temperature, incubation period, nitrogen and carbon sources were investigated. The optimum pH, temperature and incubation period for enzyme production were 5.5, 30oC and 72 hrs, respectively. Sucrose at 2 % was more suitable carbon source for invertase production (144.39 U/g) and (NH4)2SO4 at 0.15 % was the ideal nitrogen source. Among different metals ions MnSO4 enhanced the enzyme productivity than other tested ions to 194.71 U/g. The partially purified enzyme was successfully entrapped in polyvinyl alcohol sponge shielded with agar starch layer (PVAsp Gs) and achieved 71% immobilization yield. The optimum conditions for immobilization were: pH 5.2, an incubation time of 15 min and a protein concentration of 250 mg/ml. Immobilized enzyme was reused 12 times with 29% activity loss. The free enzyme lost its activity completely at 70˚C after 45 minute and the immobilized form retained 80% of its activity at the same condition.The free and immobilized form reported extreme halophilic property since the highest enzyme activity was obtained between 3.5- 5 M.